The City – towards a Postmodern Multiculturalism - Kisiel, Przemysław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article characterizes multiculturalism in the modern city. It begins by analysing the notion that cultural diversity is a natural feature of the city. But the contemporary processes of cultural diffusion, globalisation and the fragmentation and recomposition of culture have a significant impact on the production of the postmodern multiculturalism of cities, which is supported by the formation of an individual level of cultural identity. The analysis also distinguishes and characterises the basic types of postmodern multiculturalism: immanent multiculturalism, instrumental multiculturalism and tourist multiculturalism.